2020
DOI: 10.4081/cp.2020.1271
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Hemoglobin, Iron, and Hypoxia beyond Inflammation. A Narrative Review

Abstract: Coronavirus disease-19 (COVID-19) has been regarded as an infective-inflammatory disease, which affects mainly lungs. More recently, a multi-organ involvement has been highlighted, with different pathways of injury. A hemoglobinopathy, hypoxia and cell iron overload might have a possible additional role. Scientific literature has pointed out two potential pathophysiological mechanisms: i) severe acute respiratory syndrome-coronavirus-2 (SARS-CoV- 2) interaction with hemoglobin molecule, through CD147, CD26 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
437
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(452 citation statements)
references
References 70 publications
6
437
1
8
Order By: Relevance
“…The low oxygen saturation observed in COVID-19 patients 14 , suggested SARS-CoV-2 infection may have an effect on erythropoiesis. In this study, we observed that COVID-19 infection results in the expansion of CECs in the peripheral blood of patients compared to healthy controls (HCs).…”
Section: Covid-19 Infection Results In the Expansion Of Cecs In The Pmentioning
confidence: 95%
See 1 more Smart Citation
“…The low oxygen saturation observed in COVID-19 patients 14 , suggested SARS-CoV-2 infection may have an effect on erythropoiesis. In this study, we observed that COVID-19 infection results in the expansion of CECs in the peripheral blood of patients compared to healthy controls (HCs).…”
Section: Covid-19 Infection Results In the Expansion Of Cecs In The Pmentioning
confidence: 95%
“…Preliminary modeling reports have suggested that SARS-CoV-2 may inhibit heme metabolism and induce hemoglobin denaturation 14 . As such, hemoglobin alteration may compromise oxygencarrying capacity of red blood cells (RBCs) in COVID-19 patients resulting in hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism occurs because SARS-CoV-2 attacks hemoglobin (Hb) groups in the red blood cells, thereby producing the release of free Fe(III) ions from the heme groups to the bloodstream [ 30 ], which in turn produces an increase in ferritin levels [ 31 ]. Hemoglobinopathy and iron dysmetabolism, mediated by the virus, may contribute to clinical syndromes highlighted during COVID-19 including oxidative stress, ferroptosis, lipid peroxidation, and mitochondrial damage, among others [ 32 ].…”
Section: Molecular Pathogenesis Of Covid-19mentioning
confidence: 99%
“…An oxygen saturation above 90% is associated with better outcomes 6 . Over 80% of COVID-19 patients in the intensive care unit have severe hypoxemia 7 . A kind of "silent hypoxia" in which COVID-19 patients deteriorate rapidly without warning and develop respiratory failure has been described 8 .…”
Section: Introductionmentioning
confidence: 99%